Crystal Violet Binding Assay for Assessment of Biofilm Formation by Klebsiella pneumoniae on Catheter, Glass and Stainless-steel Surfaces - Musleh, Rashid; Jebur, Asmaa (Iraqi Journal of Science, 2023)
In this paper, quantified study of the biofilm formed by Klebsiella pneumoniae isolated from urine specimen of patient suffering from acute urinary tract infection (UTI) on catheter, stainless-steel and glass coupon surfaces, as well as determine the relationship between time contact and biofilm progression using crystal-violet binding assay based on the values of optical density at 620nm of the crystal violet stain which bonded total biofilm biomass by resolubizing with 99.9% ethanol at the specific interval times. The result showed biofilm formed on three tested surfaces but in different degrees. According to obtained data, the catheter coupons presents a higher capability to attract bacteria cell and biofilm formation followed by glass surfaces while stainless-steel surfaces regard as a less attractive surfaces in bacterial adhesion and biofilm progression. The attachment of the bacterial cells on the fresh produce surfaces increase with the contact time but the increase reached a maximum at time 48h. in which, the optical densities of catheter, glass and stainless-steel coupon surfaces were (0.169 nm), (0.085 nm) and (0.07 nm) respectively. The statical analysis showed significant differences between substratum type's adherence and biofilm progression.